The evaluation of non-tariff measures and their effects on the international trade landscape and competitive positioning of Cambodia and Thailand - Kosla; Lim, Siphat (Edelweiss Applied Science and Technology, 2024)
Thailand has enacted approximately 60% of the 118 Non-Tariff Measures (NTMs) categorized as Class A: Sanitary and Phytosanitary measures, which significantly impacts agricultural exports from Cambodia. In comparison, Cambodia has established only 30 NTMs, representing about 26% of the total NTMs affecting agricultural goods exported to Thailand. This disparity underscores the necessity for a bilateral meeting between the two nations to explore opportunities for reducing NTMs in agricultural trade. Concurrently, Cambodia is making strides to improve the quality of its agricultural products to enhance export potential to Thailand. If these discussions prove fruitful, the trade processes will be streamlined, leading to a substantial increase in the exchange of agricultural products between the two countries. The government should promote private sector investment aimed at elevating sanitary and phytosanitary standards to align with international benchmarks. Specifically, attracting both domestic and foreign investment to establish agricultural product processing facilities will enable the production of finished goods, thereby boosting exports and enhancing product quality. This initiative not only addresses domestic demand for agro-industrial products but also assists in identifying markets for Cambodian farmers.